The incidence of vasovagal reactions during earlobe piercing - Xie, Zi-ao; Zhang, Kai-li; Han, Fang; Tang, Meng-yao; Chen, Jue-wei; Liu, Guang-peng (Frontiers in Medicine, 2023)
Background Vasovagal reactions are common amongst patients with a fear of needles receiving injections or during venipuncture, but they are rarely studied in healthy people undergoing earlobe piercing. The purpose of this prospective study was to evaluate the incidence and the features of vasovagal reactions observed during earlobe piercing. Methods Thousand eight hundred and sixty six participants aged older than 13 years had their earlobes pierced in our department from January 2020 to January 2022. When vasovagal reactions occurred during the procedure (e.g., dizziness, pallor, diaphoresis, and faintness, etc.), they were recorded and more detailed demographic information was collected. Results A total of 196 cases of vasovagal reactions were reported in females amongst 1,866 participants, including 58 who actually lost consciousness during earlobe piercing. The incidence of vasovagal reactions and vasovagal syncope was 10.5 and 3.11% respectively. All syncopal reactions occurred in persons younger than 30 years. Conclusion Vasovagal syncope is often very sudden and occurs without warning. Practitioners need to be familiar with these reactions, and prevent people from an unpredictable fall and subsequent injury during ear piercing.